2021
DOI: 10.14744/eej.2021.96268
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological investigation of dental pulp reactions related to periodontitis

Abstract: Objective: Since the 1960s, there has been contradictory evidence regarding the association between periodontal pathology and the status of the pulp. The purpose of this study was to evaluate the histopathological changes of pulp tissue with severe periodontal disease, including vertical bone loss involving the major apical foramen, and compared them with the histological pulpal status of teeth with healthy periodontium. Methods: This case-controlled study included 35 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
5
2
Order By: Relevance
“…In contrast to the results of this study, other authors comparing teeth with various severities of attachment loss without caries and restorations [ 9 , 34 , 38 , 40 ] reported that periodontal disease can accelerate the pulp senescence process due to its interference with the nutritional supply of the pulp and concluded that periodontitis can cause the development of pulp calcifications and fibrosis [ 37 ].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In contrast to the results of this study, other authors comparing teeth with various severities of attachment loss without caries and restorations [ 9 , 34 , 38 , 40 ] reported that periodontal disease can accelerate the pulp senescence process due to its interference with the nutritional supply of the pulp and concluded that periodontitis can cause the development of pulp calcifications and fibrosis [ 37 ].…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast to the results of this study, other authors comparing teeth with various severities of attachment loss without caries and restorations [9,34,38,40] reported that periodontal disease can accelerate the pulp senescence process due to its interference with the nutritional supply of the pulp and concluded that periodontitis can cause the development of pulp calcifications and fibrosis [37]. is could be explained by the existence of an association between pulp calcification and the presence of carious lesions and restorations and not necessarily the presence of attachment loss.…”
Section: Association Between Attachment Loss and Pulpalcontrasting
confidence: 89%
See 1 more Smart Citation
“…Sustained expression of CGRP will produce fibrosis of the tissue due to hyalinization and reduction of blood vessels replaced by mineralized tissue, thus an irreversible state will be produced in the pulp, reaching necrosis, and therefore, magnifying the inflammatory response of PDL and accentuating resorption processes (Fig. 1 ) ( 6 , 12 , 29 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiological factors of this process are still unknown; however, they are associated with different factors, such as trauma, pulp degeneration, orthodontic treatment, periodontal disease, caries, operative procedures, pulp inflammation, systemic diseases, or genetic conditions [9][10][11][12][13]. This process used to be associated with age; however, it has been observed that they are also found in young patients and in teeth that have not yet erupted [14].…”
Section: Introductionmentioning
confidence: 99%